TRANSHUMANISM AS A PHILOSOPHY OF MATERIAL TRANSFIGURATION: A CRITICAL ANALYSIS - Michael M. Uzomah; Undiekeye S. Attoh (Social Sciences, Humanities and Education Journal (SHE Journal), 2020)
This paper is a critical expository analysis of the controversial philosophy of transhumanism. The method adopted in this philosophical paper is the expository analytic method. The analysis established that transhumanism is both a biotechnological aspiration as well as a philosophical vision of a material transfiguration of human condition and experience which ultimate culmination is the man-technology singularity or convergence. This paper concludes that notwithstanding contending voices and the pertinent questions raised regarding the moral standing of transhumanist philosophy and their radical dreams for humanity; one fact remains incontestable- the fact that their promises are relishing, enticing and impressive. With regard to whether or not humanity can attain the height envisioned by transhumanist, we confidently hold that the unprecedented legacies and achievements of science and technology overwhelmingly affirm the high probability of the realization of the material transfiguration of humanity.